Comparative study of motor cortical excitability changes following anodal tDCS or high‐frequency tRNS in relation to stimulation duration. Issue 19 (30th September 2020) - Haeckert, Jan; Lasser, Christoph; Pross, Benjamin; Hasan, Alkomiet; Strube, Wolfgang
Abstract: Background: In this study, we investigate the capacity of two different non‐invasive brain stimulation (NIBS) techniques (anodal transcranial direct current stimulation (anodal tDCS) and high‐frequency transcranial random noise stimulation (hf‐tRNS)) regarding the relationship between stimulation duration and their efficacy in inducing long‐lasting changes in motor cortical excitability. Methods: Fifteen healthy subjects attended six experimental sessions (90 experiments in total) and underwent both anodal tDCS of 7, 13, and 20 min duration, as well as high‐frequency 1mA‐tRNS of 7, 13, and 20 min stimulation duration. Sessions were performed in a randomized order and subjects were blinded to the applied methods. Results: For anodal tDCS, no significant stable increases of motor cortical excitability were observed for either stimulation duration. In contrast, for hf ‐tRNS a stimulation duration of 7 min resulted in a significant increase of motor cortical excitability lasting from 20 to 60 min poststimulation. While an intermediate duration of 13 min hf‐tRNS failed to induce lasting changes in motor cortical excitability, a longer stimulation duration of 20 min hf‐tRNS led only to significant increases at 50 min poststimulation which did not outlast until 60 min poststimulation. Conclusion: Hf‐tRNS for a duration of 7 min induced robust increases of motor cortical excitability, suggesting an indirect proportional relationship between stimulation duration and efficacy. While hf‐tRNS appeared superior to anodal tDCS in this study, further systematic and randomized experiments are necessary to evaluate the generalizability of our observations and to address current intensity as a further modifiable contributor to the variability of transcranial brain stimulation. Abstract : In the case of anodal tDCS, we did not observe stable increases of motor cortical excitability for either stimulation duration. By contrast, hf‐tRNS for a stimulation duration of 7 minutes resulted in a significant increase of motor cortical excitability lasting from 20 to 60 minutes post stimulation. In context of the ongoing debate regarding contributing factors to variability following non‐invasive transcranial brain stimulation, the findings of our experimental comparative study substantiate circumstantial yet novel evidence for a potential indirect proportional relationship between stimulation duration and efficacy in the case of hf‐tRNS.